Back to the classics 2: re-reading the Emanuel Saxe protestant ethic and the social ethic in the USA for accounting. (1st January 2014) - Tinker, Tony; Sy, Aida
Daniel Gross wrote in the New York Times International Edition, in July 2009, that the financial meltdown has sent scholars running to the classics to make sense of the slow-burning financial crisis. The antics of Ponzi artist Bernie Madoff have revived interest in The Great Gatsby (Scott Fitzgerald, 1950) and much more presciently the earlier character Augustus Melmott in Anthony Trollope's 19th Century villain in The Way We Live Now (republished in 1941 by Penguin Press). Now, hard-core free-marketeers like Posner (2009) have begun questioning the efficacy of capitalism. They are turning to the previously forbidden works of Karl Marx. Most of these classical critiques of capitalism still remain cited but rarely carefully read. This remains true of the writings of Emanuel Saxe and his protege Abraham Briloff, both who are now sadly departed. In this spirit, we are publishing the hitherto unpublished lectures of Emmanuel Saxe.